Analisis Keuntungan, Skala Usaha dan Efisiensi Ekonomi Relatif Usaha Budidaya Lele Dumbo Di Kota Bengkulu - Budiman Sakti (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2018)
This relative economic efficiency study uses Cobb-Douglas profit function. Besides being able to compare the efficiency level between two groups or more, use this profit function to find out whether the maximal short-term profits have been achieved and how the scale of the business is.The result of research shows the variable input factor and fixed input together effect on the profit of dumbo catfish culture business. As for the input variables comprised of the prices of which are: organic fertilizer, inorganic fertilizer, seed catfish, feed pellets, feed Dawu (small dried shrimp), drugs and labor. The fixed input consists of the pool area, the required capital (invested) and the long catfish cultivation. Among the various inputs partially, the inputs that affect the actual profit of dumbo catfish culture business is the area of the pond. Maximum short-term gain in cultivation of dumbo catfish has not been achieved. Of the seven input variables in the physical sense, only four were optimal use of inputs, namely organic fertilizers, inorganic fertilizers, feed and medicines Dawu. The state of the business scale indicates the presence of symptoms leading to increased scale of business (increasing return to scale). The comparison of economic efficiency by area of pond shows the existence of level of efficiency, that is the broader the pond of cultivation the higher the efficiency level. In addition, there is a similar degree of economic efficiency between farmers who use concrete ponds with farmers who use land ponds.